Comparative study of antibacterial activity and phytochemical analysis of stem, root and leaf extracts of Paederia foetida L. against phytopathogenic bacteria - Namsena, Piyarat; Maneetap, Juthaphak; Phonpheng, Duangkamon; Ngamsane, Walita (Agriculture and Natural Resources, 2019)
Paederia foetida L. (Skunk vine) is an indigenous weedy plant which is also known to have antimicrobial activity and to possess a broad spectrum of uses for medicinal purposes and as a food ingredient, but its beneficial effects for agriculture are still unknown. The objectives of this study were to determine the anti phytopathogenic bacterial activity and phytochemical composition of crude extracts from different parts of P. foetida using 95% ethanol as a solvent and screening of crude extracts for antibacterial activity using the agar disc diffusion method. The results showed that the crude extract of roots mixed with stems and leaves of P. foetida (1:1:1 weight per weight) at a concentration of 100 mg/mL had highly effective antibacterial activity with inhibition zone diameters of 10.00 mm, 7.00 mm and 10.33 mm for Xanthomonas campestris, Erwinia carotovora and Ralstonia solanacearum, respectively. The minimal inhibitory concentrations of P. foetida crude extract for inhibition of X. campestris and R. solanacearum were ≥ 6.25 mg/mL and ≥ 3.15 mg/mL for E. carotovora and the minimal bactericidal concentrations of X. campestris, E. carotovora and R. solanacearum were 25 mg/mL, 6.25 mg/mL and 12.5 mg/mL, respectively. The results of phytochemical analysis of the P. foetida crude extracts showed that ferulic acid and luteolin were the major phytochemical components. These findings have provided the first report suggesting the effectiveness of P. foetida extract against phytopathogenic bacteria and revealed that the extract could be used as an alternative source of antibacterial agents for the protection of plants or crops against bacterial infection.